Rape of a Biological Child and Criminal Sanctions for the Perpetrator - arief, hanafi (Scholar Center, 2025)
The phrase “rape of a biological child” refers to a situation where a parent (or another direct blood relative) commits sexual violence against their own child. Rape of a biological child in Indonesia is a serious crime regulated by various laws and regulations. This research aims to analyze the criminal provisions for sexual violence in Indonesian positive law, and analyze the criminal sanctions for perpetrators of sexual violence in Indonesian positive law. As a normative legal research, the research examines laws and regulations related to criminal act of rape. Research results: The crime of sexual violence as a whole is regulated in the Criminal Code (KUHP), Human Rights Law Number 39 of 1999, Law on the Elimination of Domestic Violence Number 23 of 2004. And specifically against children as victims is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection; The crime of sexual violence as a whole is regulated in the Criminal Code (KUHP), Human Rights Law Number 39 of 1999, Law on the Elimination of Domestic Violence Number 23 of 2004. And specifically against children as victims is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection; Criminal sanctions for perpetrators of sexual violence in the Criminal Code against minors are formulated in Article 285 of the Criminal Code, namely a maximum prison sentence of twelve years. Meanwhile, in the Child Protection Law, imprisonment based on Article is a minimum of 5 (five) years and a maximum of 15 (fifteen) years and a maximum fine of IDR 5,000,000,000.00 (five billion rupiah). In the case of a crime committed by a parent, guardian, child caregiver, educator, or education personnel, the penalty is increased by 1/3 (one third) of the criminal threat as referred to in paragraph (1)